Impact of the clam Arca zebra artisanal fishery upon the population of the neogastropod Voluta musica in eastern Venezuela - Peralta, Ana Carolina (2016)
An important ark clam (Arca zebra) artisanal fishery takes place in the east region of Venezuela. Besides the target species, trawling extracts a significant bycatch of several mollusk species including the gastropod Voluta musica, a threatened species according to the Ven ezuelan Red List of Endangered Species. In this paper we evaluate: 1) the composition of mollusk species in the bycatch, 2) the number of individuals of V. musica caught as bycatch and, 3) the abundance and size structure of the exploited populati on. Each fishing night, about 27,830 m2 are trawled by each boat extracting on the average 607 kg of A. zebra meat and 19 kg of V. musica (whole shelled animal). This fishery activity potentially captures ~30,000 kg of ark clam meat and 922 kg of V. musica in one week (~95 snails/fishing night/boat). The size structure of the V. musica population at the ark clam bed is significantly smaller than in other nearby sites not impacted by trawling fishing activities. Non-targeted species extracted in the bycatch but consumed by the local inhabitants include the gastropods Chicoreus brevifrons, Phyllonotus margaritensis, P. pomum, Fasciolaria tulipa, Strombus pugilis, a few Trochidae species, and the bivalves Pinctada imbricata, Spondylus americanus, Anadara florid ana, A . notabilis, and Trachicardium muricatum. Individuals of V. musica along with several invertebrates are discarded. We recommend that V. musica should not be neglected as a conservation target, and despite that A. zebra fisheries are considered “artisanal”, that more strict regulations should be established on it.